Structural stability of decorative ZrNxOy thin films - Carvalho, P. (2005)
ZrNxOy thin films were prepared by rf reactive magnetron sputtering. The thermal stability of the coatings was tested in vacuum for an annealing time of 1 h in the temperature range 400-800 °C. Residual stresses originated by the deposition process were partially or almost completely released with the annealing, which is consistent with the X-ray diffraction results. Samples with low oxygen fraction (0.10 < fO2 < 0.22) showed no significant changes in hardness after thermal annealing at 800 °C. For intermediate and high oxygen fractions, an initial decrease in hardness at 600 °C annealing is followed by an inversion at the highest temperatures (700 and 800 °C, respectively), resulting from possible oxide phases crystallization, defect annealing at high temperatures and some extended phase segregations. The increase in the oxygen fraction is followed by a decrease of hardness in the as-deposited samples towards the values of "pure" ZrO2. No significant changes in colour were observed with the annealing.